Viruses as vectors for the delivery of gene-editing reagents - Ellison, Evan E. (Burleigh Dodds Series in Agricultural Science, 2021)
A significant challenge for plant gene editing is the delivery of editing reagents to germline or regenerable cells to recover heritable genetic modifications. Reagent delivery using biolistics or Agrobacterium is only possible with a limited range of species and genotypes, and inefficient editing or lengthy tissue culture steps further limit throughput. Viruses are natural vectors for nucleic acids, and both DNA and RNA plant viruses have been engineered to extend or replace conventional vectors for delivery of gene editing reagents. Here, we review aspects of viral biology essential for engineering vectors, highlight landmark studies using viruses to overcome traditional limitations in gene editing, and outline important considerations for the use of viral vectors in new systems or for new targets. Motivated by fundamental differences in both their infection modes and utility as vectors, DNA and RNA viruses are treated separately.